Idiosyncratic and Aggregate Time-Varying Mutation Rates in Coordination Games - Harold Houba; Alexander F. Tieman (Tinbergen Institute, 2001)
We extend the standard evolutionary model of Kandori, Mailath, andRob (1993) to incorporate time-varying aggregate and idiosyncraticshocks separately in coordination games.We show that both types of shocks have a different effect on theinvariant distribution over the different equilibria of dthe game.While idiosyncratic shocks are shown to be neutral, the aggregateshocks introduce a systematic bias against the risk dominantequilibrium.Different from Kandori, Mailath, and Rob (1993) we derive a sufficient conditionunder which this bias prevents equilibrium selection with probability one.
Keywords: 330; Spieltheorie; Schock; Theorie